Implementation of Hubbard ACT in the United States Military Sole Survivor Policy - Vanesha Salsabila Keisya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses the influence of the Sole Survivor Policy on US military policy. Under the “Sole Survivor Policy” of the United States Department of Defense, service members who lose all their family members in war cannot be reassigned to a combat zone and will be 'honorably discharged' from the military. It aims to protect “the last son to carry the family name”. This research focuses on the case of the Hubbard brothers who became the forerunner of the Hubbard Act, which was passed by President George W Bush on August 29, 2008. This policy also resulted in veterans who were honorably discharged before the end of their contract not receiving adequate benefits. This has certainly harmed the fundamental rights of war veterans who have fought for their country, but are not given the rights they deserve. The method used in this research is normative juridical research method. The data used is secondary data. The data is presented qualitatively and analyzed descriptively. The result of this research is that the Hubbard Act, which is outlined in a United States public document entitled PUBLIC LAW 110-317, closes the gap in the existing “Sole Survivor” policy by providing veterans with a number of benefits that have been offered to other honorably discharged military members.